Upper extremity stress fractures in athletes: clinical features of 44 cases - Sinha, A. K.; Kaeding, C. C.; Wadley, G. M. (Clinical Journal of Sport Medicine, 1999)
PURPOSE: To review the clinical features of a large series of active patients with a stress fracture in a non-weight-bearing location of the upper extremity or ribs. DESIGN: Multicenter cross-sectional study. SETTING: Multiple academic medical centers. PARTICIPANTS: 44 patients with a diagnosis of upper extremity or rib stress fracture. MAIN OUTCOME MEASURES: Clinical features according to anatomic location, primary sport, and subdivided according to the nature of the sport-specific skills involved. RESULTS: A diagnosis of stress fracture was made in 44 patients based on history and physical examination, and confirmed by radiography, scintigraphy, magnetic resonance imaging (MRI), computed tomography (CT), or a combination of imaging techniques. Patients were subjectively divided into four categories based on the predominant type of upper extremity activity required for participation in their sport: 1) weight lifter (e.g., football, weight lifting, wrestling); 2) upper extremity weight bearer (e.g., gymnastics, diving, cheerleading); 3) thrower (e.g., pitcher, soccer goalie, javelin); or 4) swinger (e.g., golf, tennis). We noted that all fractures in the weight bearers occurred distal to the elbow, whereas in the throwers most fractures affected the shoulder girdle. Lower rib stress fractures predominated in the swingers group, whereas weight lifters had fractures located throughout the upper extremity. CONCLUSION: Stress fracture should be considered in the differential diagnosis of athletes presenting with upper extremity or rib pain of bony origin that is of insidious onset. Further study of the sport-specific patterns of injury described here may improve our ability to treat and prevent these injuries.